Studi Kritis Buku Hazihi Lugati dan al-Muyassar fi Ilmin Nahwi di Pondok Pesantren Tahfizhul Qur'an Imam An-Nasa'i Gowa - Rappung, Hasriana; Ilyas, Hamka; Abd. Rahman, Anwar (Journal of Arabic Education and Linguistic, 2023)
This research discusses the critical study of Arabic textbooks at the Tahfizhul Qur'an Imam An-Nasa'i Gowa Islamic Boarding School at the wust}a level, based on the achievement of four language skills. The aim of this research is to find out how the availability of teaching materials in the books Ha>z\ihi> Lugati> and al-Muyassar fi> 'Ilmin Nahwi fulfills the four language skills. This type of research includes library research with a qualitative descriptive analysis type. The data sources for this research are scientific literature, documents from interviews, observations, and other supporting data sources. Data is collected from references that are considered representative and from respondents who have a direct connection to the research. The data is then classified, selected and quoted according to its relevance to the problem being studied and then analyzed using a document study approach. The results of this research show, 1) The books "Ha>z\ihi> Lugati>" and "al-Muyassar fi> 'Ilmin Nahwi" are taught at the Tahfizhul Qur'an Imam An-Nasa'i Islamic Boarding School in classes VII-IX, 2 ) In the book "Ha>z\ihi> Lugati>" volumes 1-6 have facilitated four language skills with an average of each skill, namely 21.30 % istima>', 33.57 % kala>m, 23.42 % us >bah, and 21.71 % qira>'ah. This shows that there is a balance in the portion of each skill. Meanwhile, the book "al-Muyassar fi> 'Ilmin Nahwi" volume 1 has not yet facilitated a maximum of four language skills with the percentages obtained being 1.75 % istima>', 47.37 % kala>m, 42.11 % us>bah , and 8.77% qira>'ah, 3) Based on the analysis of the content of teaching materials and the number of lesson hours applied, there is a gap in achieving the Arabic language curriculum targets. So the Tahfizhul Qur'an Imam An-Nasa'i Islamic Boarding School in Gowa must immediately evaluate the target for Arabic language teaching materials at the Wust}a level.